Food colloids : proteins, lipids and polysaccharides - Dickinson, E.; Bergenstahl, B. (Woodhead Publishing in food science, technology, and nutrition., 2004)
The field of food colloids is concerned with the structural and dynamic aspects of multi-phase food systems - dispersions, emulsions, foams, gels - viewed from a physical chemistry perspective as assemblies of molecules and particles in various states of organisation. The main molecular components of food colloids are proteins, lipids and polysaccharides. The primary objective of the field is to relate the structural, stability and rheological properties of such systems to the interactions between constituent components and to their distribution between the bulk phases and various kinds of interfaces. This volume records most of the lecture programme at the international conference on "Food Colloids - Proteins, Lipids and Polysaccharides" held in Sweden on 24-26th April 1996